CHILDRENS LANGUAGE DEVELOPMENT - Wahyuni, Sri (STKIP Bina Bangsa Getsempena Banda Aceh, 2016)
The objective of this article is to describe how childrens language is developed. The development of childs language actually begun when a child was born with language or a simple talk. First language is the language that is the primary language that is acquired which is called native language or mother tongue. This study is intended to childrens language development and their social interaction. To get the data, four children asked to speak about everything of their interest. The process of recording was made as naturally as possible. All the data obtained were then used to facilitate the researcher in describing childrens talk. As the result, children direct his attention to thing that language is easy to understand and they used primary interest to help them learn the language related to their interest. They also enjoyed the repetitive events of their life and used it strategies to help them in learning a language. Children can quickly acquire new words if they always heard a new language around them and automatically the development of their language will increased faster. Children learn language through their natural desire to call an object by its name and almost all of the words their produced were not clear enough. They often used a piece of dismembered words.Â Key words: Children, Language Development